Descriptive study on substance uses and risk of sexually transmitted infections in the practice of Chemsex in Spain - del Pozo-Herce, Pablo; Baca-García, Enrique; Martínez-Sabater, Antonio; Chover-Sierra, Elena; Gea-Caballero, Vicente; Curto-Ramos, Javier; Czapla, Michal; Karniej, Piotr; Martínez-Tofe, Jesús; Sánchez-Barba, Mercedes; de Viñaspre, Regina Ruiz; Juárez-Vela, Raúl (Frontiers in Public Health, 2024)
Background In recent years, there has been an increasing use of sex-related substances (known as “Chemsex”) to facilitate, intensify, and prolong the sexual experience of men who have sex with men. This phenomenon poses a public health problem, increasing the risk of sexually transmitted infections (STIs) and mental disorders. Objective The primary aim of this study was to delve into the correlation between substance use and sexual health, specifically examining the association between different substances used and the risk of sexually transmitted infections (STIs) in the context of Chemsex in Spain. Methods An observational, descriptive, cross-sectional study was conducted among 563 Spanish participants between January and April 2023. Non-probabilistic purposive sampling was used by the investigators. The researchers administered a questionnaire to men who have sex with men who use substances, especially in the sexual sphere, in all the autonomous communities of Spain. Results 14.7% reported having practiced slamsex in the last year, and 17.94% were diagnosed with a Sexually Transmitted Infection in the previous 6 months. Of these, 21% were on PREP treatment, with the main STIs being gonorrhea (p < 0.001), chlamydia (p < 0.001), genital herpes (p = 0.020), and syphilis (p < 0.001). The 63.7% used methamphetamines as the main drug in the practice of chemsex. Discussion Chemsex in Spain is linked to a high prevalence of STIs, especially gonorrhea and chlamydia, even among those on PrEP treatment. The use of various drugs during chemsex, such as amyl nitrite, GHB, ecstasy, and others, correlates with higher rates of STIs, highlighting the need for interventions to reduce risk and harm. The drugs most associated with slamsex include ketamine, mephedrone, and methamphetamine, underscoring the importance of addressing the risk behaviors associated with this activity. Conclusion This study shows that chemsex appears to be associated with a high prevalence among men who have sex with men. Who use multiple substances in a sexual context, and are particularly exposed to sexually transmitted infections (STIs), indicating a particular need for STI prevention and care in this group.